Leadership's Approach to Overcoming Resistance to Organizational Change - Destian, Nanda; Johari, Fuadah Binti (Malacca: Journal of Management and Business Development, 2025)
There is a lack of transparency in the communication of many decisions to staff, as well as inadequate capabilities, and the findings of Lurah's research remain closed.  Good communication, whether with employees or the general public, will influence the development of the planned work program, the next step after establishing the organization's vision, according to Lurah.  Lurah has failed to grasp the village organization's goal and vision, and the junior high school teachers' educational backgrounds and lack of experience in government make for a very inexperienced workforce.  Lurah is still in the dark about its rivals and has no strategy in place.  The character of Lurah's history and his reluctance to comply with the rules dominate the program and his unwillingness to make decisions.  As a result of this study's problem-solving efforts, we now know that there has to be a system of rotating jobs depending on competency and knowledge; Lurah was also successful in recognizing the inappropriateness of the author's job description.  Lurah has to step up her level of dedication, engagement, and participation; A Lurah's mounting requires familiarity with the Auth and regulations;  Task and competency fields for task delegation;  The educational, skill, and loyalty requirements for Lurah's background must be satisfied.